Sistem Informasi Kawasan Perbatasan Negara Kalimantan Utara - Hidayatul Muttaqien; Hutami Endang; Abdul Hakim (Empowerment: Jurnal Pengabdian Masyarakat, 2022)
North Kalimantan Province has many challenges to achieve its global target because this province is still dealing with complex information system problems, such as the information related to the Indonesia-Malaysia border area. Dissemination of information from authority in the city (government) to local government is challenging. The slow dissemination of information causes some activities to be constrained. From this case, the researcher attempt to provide a solution to support the system needs of the North Kalimantan government. A web-based system and a mobile-based application that is integrated with the Global Positioning System (GPS) so that a GIS-based system conceivable to be constructed. The following is an overview of the integrated Information System Management concept. From the results of the research, it is concluded that the information system for the border area of ​​North Kalimantan is expected to provide effortless information from the rural to sub-district and to the district government levels. By means of this  information system, it is expected to be able to support the system needs of the North Kalimantan Government. This information system is expected to support the needs of the North Kalimantan government information system. The information systems that are expected to be constructed later are web-based information systems and mobile-based applications that are integrated with the Global Positioning System (GPS).